2021
DOI: 10.1097/cce.0000000000000572
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Bleeding in Critically Ill Children With an Underlying Oncologic Diagnosis

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, the investigators used the WHO bleeding scale which may not be as relevant for critically ill patients (12). When comparing our study with a 2018 retrospective cohort similar to our population (7), using the BASIC definition, the finding of 9% experiencing at least one severe bleeding event during admission is similar.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, the investigators used the WHO bleeding scale which may not be as relevant for critically ill patients (12). When comparing our study with a 2018 retrospective cohort similar to our population (7), using the BASIC definition, the finding of 9% experiencing at least one severe bleeding event during admission is similar.…”
Section: Discussionmentioning
confidence: 65%
“…Although bleeding has been described in the general PICU population, 2014-2020 (1)(2)(3), as well as during extracorporeal membrane oxygenation 2012-2020 (4)(5)(6), there are limited data focusing on bleeding and transfusion practices in critically ill children with malignancy. One retrospective cohort from 2018 reported that 9% of critically ill children with malignancy had severe bleeding (7). Children with cancer may be more vulnerable to bleeding events given frequent thrombocytopenia, chemotherapy, and radiation exposure, numerous procedures and surgeries, and reduced ability to recover from bleeding events secondary to bone marrow suppression.…”
Section: E603mentioning
confidence: 99%
“…Using the BASIC definition, our finding that severe bleeding in children following CPB is associated with poorer clinical outcomes mirrors that reported in a heterogenous prospective cohort of critically ill children, 16 as well as those with an underling oncologic diagnosis. 17 Previous studies, using a variety of definitions, have reported the rate of severe bleeding following cardiopulmonary bypass in children to range from 3 to 42%. 12 Various studies have concluded that younger age is associated with an increased risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Using the BASIC definition, our finding that severe bleeding in children following CPB is associated with poorer clinical outcomes mirrors that reported in a heterogenous prospective cohort of critically ill children, 16 as well as those with an underling oncologic diagnosis. 17…”
Section: Discussionmentioning
confidence: 99%